Developing a digital tool to support avoidance of research repetition in the Humanities and Social Sciences - Milton, M. A.; Lankathilake, M.A.; Kuruppu, D.C. (Library, University of Colombo, Sri Lanka, 2018)
Research in Humanities and Social Sciences (HSS) in Sri Lanka are increasing but most related articles are published in local journals in English, Sinhala and Tamil languages in print mode. Therefore researchers do not have an opportunity to be included in reputed indexing/abstracting services and they do not have an opportunity to conduct comprehensive analysis of literature on what has been conducted in their disciplines. As a result many HSS research may encount problems of getting duplicated. Development of a database is proposed as the most suitable solution. Accordingly, the objective of this study was to develop a database of all English, Sinhala and Tamil journals and conference proceedings published in Sri Lanka. As the first step a model was developed to construct a database. D-space open source software was used to develop the repository for long-term storage, access and preservation of digital content. Consequently, a prototype was developed. In the database subject headings under HSS considered as communities and the sub divisions of main subject areas as sub communities. An item menu was created which contains meta data. The metadata for the database were identified as bibliographic information such as author name, authorship, title, citations, year, publisher details, journal name, volume, page numbers or conference name place and pages numbers. The created database consists of different authentication levels for uploading and online editorial process. The second phase of the study will consider uploading of documents by providing key words and subject titles using standard subject thesaurus.
Keywords: database; Humanities; research duplication; Social Sciences; Sri Lanka